Study of Morphological Characteristics of Electrical Apparatus Arc by High-Speed Photography and Image Processing Technology. Issue 1 (March 2014) - Xiangjun, Liu; Taishou, Lan; Baohe, Xie
The images of arc motion of the electrical apparatus during breaking process are taken by the test device based on high-speed camera in this paper. By means of a series of processing methods such as median filtering, Gaussian filtering, grayscale transformation and binary conversion, the arc images are processed and the total pixel values of arc images are calculated to complete the numerical representation of the arc morphology. The relationship between the arc pixel area and time during the whole process from arc ignition to extinction is studied. It can provide the basis for the study of arc motion discipline.